ANALISIS KUALITAS SISTEM LAYANAN PENILAIAN BUKU PENDIDIKAN AGAMA (SiLPBPA) MENGGUNAKAN METODE SYSTEM USABILITY SCALE (SUS) DAN PENGEMBANGANNYA MENGGUNAKAN SCRUM BERBASIS WEB - Asep Erlan Maulana; Abu Khalid Rivai; Sarwani Sarwani (JURNAL TEKNIK INFORMATIKA, 2020)
SiLPBPA version 1.0 is implemented in the Religious Education Book Assessment Service activities. However, there are many obstacles and problems, namely that some system functions do not match the needs that support their activities. The purpose of this research is to conduct quality analysis and develop SiLPBPA. The methodology for conducting quality analysis is the System Usability Scale (SUS), and its development uses the Agile method with a Scrum framework. The results show that the system's quality gets a score of 71, which means the system is Acceptable, is in Predicate C, and with a good rating. However, some users gave some suggestions on the questionnaire. These suggestions are evaluated, which are used as the basis for system development. The results of developing using Scrum can be completed within 65 hours of the target time of 70 hours shown on the Burndown Chart. Some system functions can be completed properly. This was proven at the Sprint Review event, the Scrum Team and Stakeholders who attended approved the Product Increments that had been developed in all Sprints. So that SiLPBPA can be used in the next Education Book Assessment service activities.